FENOMENA HADITS POPULER DI MEDIA SOSIAL DAN IMPLIKASINYA TERHADAP PEMAHAMAN UMAT - Nisrina Fikria Nabila; Miftahul Huda (STKIP Subang, 2026)
In the digital disruption era, social media has become a primary space for spreading religious information, including the Hadith of Prophet Muhammad, which is often detached from the verification of sanad and scientific context. The lack of hadith studies literacy among the public triggers a gap between the popularity of hadith content and its authenticity quality. This study aims to dissect the phenomenon of popular hadith dissemination on social media and analyze its implications on the pattern of religious understanding of the ummah. This research employs a qualitative approach with library research. Data were collected through documentation and virtual observation of viral hadith content across various social media platforms from 2023 to 2025, which were then analyzed using content analysis and hadith verification (takhrij al-hadits). The results indicate a significant gap between the virality level of hadith and its authenticity status, where many weak or fabricated hadiths are widely accepted because they are packaged with emotional narratives. This phenomenon has shifted religious authority from scientific sanad to digital popularity, triggering rigid textualist understanding and eroding the tradition of referring to classical texts. Therefore, integrating the principles of hadith studies into the public's digital literacy is crucial to creating a healthy and accurate religious information ecosystem.